2019
DOI: 10.1002/ijc.32626
|View full text |Cite
|
Sign up to set email alerts
|

Helminth‐derived molecules inhibit colitis‐associated colon cancer development through NF‐κB and STAT3 regulation

Abstract: Inflammation is currently considered a hallmark of cancer and plays a decisive role in different stages of tumorigenesis, including initiation, promotion, progression, metastasis and resistance to antitumor therapies. Colorectal cancer is a disease widely associated with local chronic inflammation. Additionally, extrinsic factors such as infection may beneficially or detrimentally alter cancer progression. Several reports have noted the ability of various parasitic infections to modulate cancer development, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Therefore, there is an urgent need to explore novel substances as therapeutic agents against CRC with few or no adverse side effects. Fortunately, several studies have shown that naturally active polysaccharides, extracted from fungi, plants, animals, algae, and lichens [3][4][5][6], possess anti-CRC properties [7,8] through a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to explore novel substances as therapeutic agents against CRC with few or no adverse side effects. Fortunately, several studies have shown that naturally active polysaccharides, extracted from fungi, plants, animals, algae, and lichens [3][4][5][6], possess anti-CRC properties [7,8] through a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-Promoting Pathways. The transcription factors NF-κB and STAT3 are involved in inflammation and tumorigenesis and regulate cell survival, growth, and proliferation [97]. Many cytokines involved in the inflammatory response, such as TNF and IL-1, are involved in the activation of the NF-κB signaling pathway [88].…”
Section: Oxidative Stress and Tumorsmentioning
confidence: 99%
“…In the Th1 cell-mediated EAE animal model, β-elemene improves the course of EAE mice by inhibiting RORγt, which is activated by the IL-6 and STAT3 pathways [129]. The NF-κB and STAT3 pathways play key roles in the formation of the inflammatory environment, as well as in the development, invasion, and metastasis of tumors [97]. The inhibitory effect of β-elemene on these two pathways has shown good antiinflammatory and anticancer applications, but this requires further research.…”
Section: β-Elemenementioning
confidence: 99%
“…For immunohistochemical analysis, the sections were deparaffinized in xylene and then rehydrated with graded alcohols and processed as reported previously [69]. The sections were incubated overnight at 4 • C with the respective primary antibodies diluted in 1× PBS (anti-E-cadherin, 1:300, cell signaling; anti-β-catenin, 1:200, GeneTex, Irvine, CA, USA) and then developed following the conventional technique.…”
Section: Histologic Analysismentioning
confidence: 99%